ANALISIS KAIDAH DAN DHOWABITH DALAM PENAFSIRAN KALIMAT AL-QUR’AN: STUDI KUALITATIF BERBASIS TADABBUR - Muhammad Yasir; Budi Suhartawan (Sekolah Tinggi Ilmu Al-Qur'an Ar-Rahman, 2026)
This study investigates the application of qawāʿid (principles) and ḍawābiṭ (methodological parameters) in interpreting Qur’anic expressions through a tadabbur-based approach. The study addresses a critical gap in contemporary Qur’anic studies, namely the tendency toward partial and overly literal interpretations that prioritize linguistic analysis while neglecting the integration of authoritative interpretative sources. This research aims to develop a systematic and integrative framework for understanding Qur’anic language that is both methodologically sound and contextually relevant. Employing a qualitative method with a library research design, this study analyzes classical and contemporary tafsir literature to identify patterns, principles, and interpretative structures. The findings demonstrate that valid Qur’anic interpretation requires the integration of three key dimensions: linguistic analysis, contextual understanding (siyaq), and authoritative sources, including the Qur’an, hadith, and interpretations of early Muslim scholars. Furthermore, this study proposes a multi-layered and cyclical interpretative model, in which interpretation begins with the Qur’an, is clarified through hadith and early authorities, analyzed via linguistic and contextual approaches, and ultimately revalidated against the Qur’an. This model serves as a methodological control mechanism to ensure interpretative accuracy and prevent deviation. The study contributes to Qur’anic hermeneutics by offering an integrative framework that bridges classical scholarship and contemporary interpretative needs.